2014
DOI: 10.1071/wf12206
|View full text |Cite
|
Sign up to set email alerts
|

Sagebrush steppe recovery after fire varies by development phase of Juniperus occidentalis woodland

Abstract: Abstract. Woodland ecosystems of the world have been changed by land use demands, altered fire regimes, invasive species and climate change. Reduced fire frequency is recognised as a main causative agent for Pinus-Juniperus L.(piñon-juniper) expansion in North American woodlands. Piñon-juniper control measures, including prescribed fire, are increasingly employed to restore sagebrush steppe communities. We compared vegetation recovery following prescribed fire on Phase 2 (mid-succession) and Phase 3 (late-succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 72 publications
(113 reference statements)
4
88
0
Order By: Relevance
“…Increases in annual weed cover the first few years after tree reduction treatments may give way to perennial dominance in time, but differential site conditions and posttreatment management result in a wide array of long-term responses in dominance from annual weeds to desirable perennials (Bates et al 2000;Bates et al 2013;Miller et al 2005Miller et al , 2014. Across our regional study, cheatgrass cover was increased by burning at low to high phases of infilling, and at mid to high phases of infilling by mechanical treatments (Fig.…”
Section: Cheatgrass Invasibility In Relation To Site Treatment and mentioning
confidence: 78%
See 2 more Smart Citations
“…Increases in annual weed cover the first few years after tree reduction treatments may give way to perennial dominance in time, but differential site conditions and posttreatment management result in a wide array of long-term responses in dominance from annual weeds to desirable perennials (Bates et al 2000;Bates et al 2013;Miller et al 2005Miller et al , 2014. Across our regional study, cheatgrass cover was increased by burning at low to high phases of infilling, and at mid to high phases of infilling by mechanical treatments (Fig.…”
Section: Cheatgrass Invasibility In Relation To Site Treatment and mentioning
confidence: 78%
“…Miller et al (2014) reported that burning initially decreased perennial herbaceous cover on these sites, but that cover recovered by the third year after treatment. In a study of western juniper woodlands on Steens Mountain, southeastern Oregon, Bates et al (2013) found recovery of perennial herbaceous cover after burning Phase II (codominant trees with shrubs and perennial herbs) woodlands, but Phase III (dominant trees) woodlands had limited perennial herbaceous cover both before and after severe fire. We expect continued recovery of perennial herbaceous cover on our sites where cheatgrass cover is limited and residual perennials are already well adapted to the environmental conditions (Rew and Johnson 2010).…”
Section: Should Treatments Target a Specific Phase Of Infilling?mentioning
confidence: 96%
See 1 more Smart Citation
“…Land managers reduce live tree dominance by prescribed fire and various mechanical means such as manual or hydraulic cut-and-drop or by shredding standing trees. To restore or maintain resilient ecosystems, managers should treat infilling areas well in advance of a suspected ecological threshold of tree cover (Bates et al 2013;Roundy et al 2014). This threshold tree cover has conceptually been considered to be an upper ratio of tree to total perennial cover beyond which fuel loads are high and understory residual plants (e.g., shrubs and perennial herbaceous plants) and seed banks are so limited that invasive annuals are much more likely than desirable perennials to dominate after fire or fuel-control disturbances .…”
Section: Introductionmentioning
confidence: 99%
“…Sites in the late stage of piñon and juniper expansion and infilling (Phase III from Miller et al 2005) have reduced fire frequency (due to decreased fine fuels), but are prone to higher severity fires (due to increased woody fuels) which significantly reduces the likelihood of sagebrush habitat recovery (fig. 5) (Bates et al 2013). Even before direct habitat loss occurs, sage-grouse avoid or are negatively associated with conifer cover during all life stages (i.e., nesting, broodrearing, and wintering; Doherty et al 2008Doherty et al , 2010aAtamian et al 2010;Casazza et al 2011).…”
Section: Effects On Sage-grouse Habitat Selection and Population Dynamentioning
confidence: 99%